Climate Policy Beyond Kyoto: Quo Vadis? A Computable General Equilibrium Analysis Based on Expert Judgements - Christoph Böhringer; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Despite of the apparent failure of the Kyoto Protocol with respect to environmental effectiveness, it has established a broad international mechanism that might be able to provide a global reduction of greenhouse gas emissions during a second commitment period. In this paper we investigate the likely future of post-Kyoto policies. Our primary objective is to identify policy-relevant abatement scenarios and to quantify the associated economic implications across major world regions. Based on a cross-impact analysis we first evaluate an expert poll to select the most likely post-Kyoto climate policy scenarios. We then use a computable general equilibrium model to assess the economic implications of these key scenarios. We find that post-Kyoto agreements are likely to cover only small reductions in global greenhouse gas emissions with abatement duties predominantly assigned to the industrialized countries while developing countries do not make any commitments, but can sell emission abatement to the industrialized world. Equity rules to allocate abatement duties are mainly based on the sovereignty principle or ability-to-pay. Global adjustment costs arising from post-Kyoto policies are very moderate but fuel exporting countries are likely to face quite considerable costs because of adverse terms-of-trade effects on fossil fuel markets.
Keywords: D58; Q25; Q21; 330; climate policy; cross-impact analysis; computable general equilibrium modeling; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Szenario-Technik; Wirtschaftspolitische Wirkungsanalyse; Allgemeines Gleichgewicht; Welt